CONGENITAL DIAPHRAGMATIC HERNIA - DIAGNOSIS, TREATMENT AND FAMILY PLANNING - Mirjana Kjaeva Pejkovska; Maja Pejkovska Ilieva (Македонско лекарско друштво = Macedonian medical association, 2025)
Introduction. Congenital diaphragmatic hernia is a rare structural and genetic disorder. Early diagnosis, proper treatment and expectance of the outcome in terms of future family planning are needed. Aim. To increase the awareness of early diagnosis and to present the current protocols for diagnosis, treatment and family planning if congenital diaphragmatic hernia occurs, particularly in early childhood. Methods. For the purpose of this retrospective study, 20 mothers who gave birth to children with congenital diaphragmatic hernia were enrolled. They had been given questionnaires regarding the timing of their fetus’s diagnosis, the treatment that followed, and the frequency of this condition in their family. Before the treatment, parents of the patients signed a consent form. Their data were collected and analyzed in the period of two years. Results. Early diagnosis can be life saving because the baby needs to be intubated as soon as the mother gives birth. Some mothers had to plan their deliveries ahead in institutions with highly developed intensive care, with Discussion. Early diagnosis is of crucial importance for timely preparation and treatment of both mothers and babies. ECMO treatment, to provide the best treatment protocol for better quality of life for both mother and child. In the literature the need for sterilized conditions during the treatment is described because of the possible complication such as sepsis caused by healthcare-associated infections. Conclusion. Congenital diaphragmatic hernia is a condition for which awareness must be raised for proper diagnosis, treatment and family planning.
Keywords: congenital diaphragmatic hernia; awareness; diagnosis; treatment